Perancangan Sistem Informasi Penjualan Busana Muslim Berbasis Web di PT Megah Madani - Santika Rahayu; M. Masnaya (Journal of Economic, Bussines and Accounting (COSTING), 2023)
ABSTRACT PT Megah Madani wrong one companies engaged in the sales industry _ fashion muslim.activities polling transaction sales at PT Megah Madani still conducted manually so that transaction sale and proof transaction online sales are often missed because deposit proof transaction conducted through message Whattsap , inside To do reporting not yet conducted by automatic so data is lacking accurate . To use resolve problems the writer designing something system information sales that can optimizing activity transaction sales the with using web media. design made _ use language PHP (PHP: Hypertext Preprocessor) programming and using the MYMSQL (My Structured Query Language) data base as data storage media , and planning system with use waterfall method . So that sales system design this could make it easy PT Megah employees Madani in polling transaction sale because it was designed simple and can be understood by employee , application system this web based also could make it easy employee in To do every transaction sale good input data or edit data, in To do checking transaction and proof transaction sales , and checking report sales . So that could minimize possible error _ occur in activity company. Keywords : Sales, Web, PHP, MYSQL, sistem information